Pain with neuropathic characteristics after surgically treated lower limb fractures: cost analysis and pain medication use - Png, ME; Costa, M; Petrou, S; Achten, J; Knight, R; Bruce, J; Keene, D (SAGE Publications, 2023)
Introduction: Neuropathic pain is prevalent among people after lower limb fracture surgery, and is associated with lower health-related quality-of-life and greater disability. This study estimates the financial cost and pain medication use associated with neuropathic pain in this group.